Anti-inflammatory actions of acupuncture - Freek J. Zijlstra; Ineke van den Berg-de Lange; Frank J. P. M. Huygen; Jan Klein (Mediators of Inflammation)
Acupuncture has a beneficial effect when treating many diseases and painful conditions, and therefore is thought to be useful as a complementary therapy or to replace generally accepted pharmacological intervention. The attributive effect of acupuncture has been investigated in inflammatory diseases, including asthma, rhinitis, inflammatory bowel disease, rheumatoid arthritis, epicondylitis, complex regional pain syndrome type 1 and vasculitis. Large randomised trials demonstrating the immediate and sustained effect of acupuncture are missing. Mechanisms underlying the ascribed immunosuppressive actions of acupuncture are reviewed in this communication. The acupuncture-controlled release of neuropeptides from nerve endings and subsequent vasodilative and anti-inflammatory effects through calcitonine gene-related peptide is hypothesised. The complex interactions with substance P, the analgesic contribution of β-endorphin and the balance between cell-specific pro-inflammatory and anti-inflammatory cytokines tumour necrosis factor-α and interleukin-10 are discussed.